Analisis Hubungan antara E-Service Quality dan Trust pada Customer Satisfaction & Behavioral Intentions Telaah pada Net Generation Konsumen Lazada Indonesia - Kevin Taslim (Ultima Management : Jurnal Ilmu Manajemen, 2015)
Internet growing very fast nowadays. One of it’s widely known application is online transaction or usually called e-commerce. This research mainly discuss about factors which affect customer behavioral intentions, including word-of-mouth, repurchase intentions and site revisit. Those factors are e-service quality, satisfaction and trust. The study uses descriptive research design, which use non-probability sampling applying judgemental sampling techniques. The data collected by spreading the questionnaire with total sample of 228 respondents who are Lazada’s customer. The hypotheses are tested with structural equation modelling. The study showed that e-service quality has indirect relationship with behavioral intentions through satisfaction. However, e-service quality is not significantly directly related with behavioral intentions. While trust are strongly related with behavioral intentions. Keywords: Electronic Commerce, E-Service Quality, Trust, Satisfaction, Online Retailing, Lazada Indonesia